Desbalance entre el sistema renina angiotensina y sistema dopaminérgico renal en la fisiopatogenia de la hipertensión arterial y daño renal inflamatorio en un modelo experimental por sobrecarga de fructuosa - Rukavina Mikusic, Natalia Lucía (2018)
The renin angiotensin system (RAS) and the renal dopaminergic system (RDS) act as autocrine and paracrine systems to regulate renal sodium management and inflammation and their alterations have been associated to the development of hypertension and renal damage.\n\nThe aim of this thesis was to demonstrate the existence of an imbalance between the RAS and RDS associated to the development of hypertension and inflammatory kidney damage in an experimental model of metabolic syndrome due to fructose overload, as well as to establish the prevention of the harmful processes, by pharmacological inhibition of RAS by losartan treatment. Finally, we studied the behavior of the urinary L-dopa/dopamine index as a potential biomarker of renal dysfunction.\n\nThe results of this thesis provide the mechanisms by which a prohypertensive and proinflammatory system, such as RAS, downregulates another antihypertensive and antiinflammatory system such as RDS, establishing a positive feedback loop that leads to hypertension and kidney inflammation due to fructose overload. Additionally, we demonstrated the potential usefulness of the L-dopa/dopamine index as a biochemical marker of renal dysfunction, earlier than microalbuminuria, and as a predictor of response to treatment and follow-up of hypertension and inflammatory kidney damage.